Microwave radiation associated with stepped leaders of negative cloud-to-ground flashes - Ahmad, Mohd Riduan; Shamsul Baharin, Shamsul Ammar; Al-Shaikhli, Taha Raad Khaleel; Sidik, Muhammad Abu Bakar; Mohammad Sabri, Muhammad Haziq; Al-Kahtani, Ammar Ahmed; Mohammad, Sulaiman Ali; Lu, Gaopeng; Zhang, Hongbo; Cooray, Vernon (Elsevier Ltd, 2022)
In this paper, Very-High Frequency (VHF) and microwave radiation pulses associated with stepped leader pulses (conventional breakdown) are examined. A total of 100 stepped leader pulses (SLPs) with the associated 100 quiet periods (QPs) from ten negative cloud-to-ground (CG) flashes within the reversal distance (<8 km) have been analyzed. The QP is defined as the period between two SLPs when no electrical activity within the fast antenna sensor bandwidth was detected. The measurement system is made up of fast antenna (FA) and slow antenna (SA) sensors, a VHF sensor (60 MHz center frequency with 40 MHz bandwidth), and a microwave sensor (0.97 GHz center frequency with 20 MHz bandwidth). The waveforms were sampled at 2.5 GHz (400 ps). The total durations of the SLPs and QPs were 2.648 ± 1.152 μs and 2.708 ± 1.670 μs, respectively. All microwave and VHF radiation waveforms have been detected as clear individual oscillating pulses. The key finding is that the microwave radiation can be classified into three categories based on the total number of detected individual oscillating pulses during the QP. Two microwave pulses detected during the QP (Category 1) are suggested to be associated with the electron avalanche/corona process at the tip of an existing negative leader and a space stem. The VHF pulses associated with the microwave pulses are suggested to be emitted by propagating streamers. On the other hand, a single microwave pulse detected during the QP (Category 2) is suggested to be emitted by the electron avalanche/corona process of a space stem. The VHF pulses associated with the microwave pulse are suggested to be emitted by propagating streamers. In both categories, 70% of the microwave radiation pulses have been observed to precede VHF radiation pulses with an average lead time of 0.848 ± 1.336 μs. The head-on collision of a downward propagating negative streamer and an upward propagating positive streamer (from space stem) emitted significant microwave radiation. A new negative leader was formed when the head-on collision took place. The microwave radiation pulses emitted by the head-on collision process were observed to precede SLPs with an average lead time of 0.423 ± 0.378 μs. Around 80% of the microwave radiation pulses preceded VHF radiation pulses with average lead time of 0.540 ± 0.596 μs. Therefore, microwave and VHF radiation pulses are suggested to be emitted by different processes of the electrical breakdown mechanism. The microwave radiation is emitted by electron avalanche/corona/head-on collision while the VHF radiation is emitted by propagating streamers.